PENGARUH KEBIASAAN BEROLAHRAGA TERHADAP TEKANAN DARAH PADA PRIA DEWASA YANG TERORGANISIR DAN TIDAK TERORGANISIR KOTA BATAM 2018 - Martin Andi Hamdjang; Rosyadi Aziz Rahmat (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Health is one of the things that is quite important in human life. Various ways have been tried to stay healthy. These efforts are promotive, preventive, curative and rehabilitative in nature. Sports is one of the cheapest and easiest preventive measures. Regular and measurable exercise will be very beneficial in maintaining a lifestyle. This type of research is analytic descriptive with a cross-sectional design conducted in September and December 2018. The population of this research is 30 members of the Mobile Brigade and 30 employees of Batam City Retribution Agency and 60 samples have been obtained and 60 samples have been included in the research criteria. Data was collected by direct observation of respondents by measuring blood pressure. Data were analyzed univariately and bivariate by computer using the chi-square statistical test. Based on statistical test results, it was found that there was a significant effect between exercise habits and blood pressure. The results of the 60 samples also showed that based on the results of the statistical test, it was found that there was a significant influence (p-value = 0,000) between exercise habits on blood pressure. From the results of the study it can be concluded that there is a significant effect between Exercise Habits Against Blood Pressure.